2022
DOI: 10.1186/s12916-022-02543-6
|View full text |Cite
|
Sign up to set email alerts
|

Characterising social contacts under COVID-19 control measures in Africa

Abstract: Background Early in the COVID-19 pandemic, countries adopted non-pharmaceutical interventions (NPIs) such as lockdowns to limit SARS-CoV-2 transmission. Social contact studies help measure the effectiveness of NPIs and estimate parameters for modelling SARS-CoV-2 transmission. However, few contact studies have been conducted in Africa. Methods We analysed nationally representative cross-sectional survey data from 19 African Union Member States, col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Since the onset of the outbreak of COVID-19 in Wuhan in December 2019, there have been numerous scientific works aimed at modelling, estimating, and forecasting the number of COVID-19 cases, deaths, recoveries, contacts and attack rates in various settings( Al-qaness et al, 2020 ; Benvenuto et al, 2020 ; Ceylan, 2020 ; Chakraborty & Ghosh, 2020 ; Dobreva et al, 2022 ; Musa et al, 2022 ; Toga et al, 2021 )–– ( Al-qaness et al, 2020 ; Benvenuto et al, 2020 ; Ceylan, 2020 ; Chakraborty & Ghosh, 2020 ; Dobreva et al, 2022 ; Musa et al, 2022 ; Toga et al, 2021 ). Most of these works were based on publicly available data, generally reported by public health authorities in an aggregated form.…”
Section: Discussionmentioning
confidence: 99%
“…Since the onset of the outbreak of COVID-19 in Wuhan in December 2019, there have been numerous scientific works aimed at modelling, estimating, and forecasting the number of COVID-19 cases, deaths, recoveries, contacts and attack rates in various settings( Al-qaness et al, 2020 ; Benvenuto et al, 2020 ; Ceylan, 2020 ; Chakraborty & Ghosh, 2020 ; Dobreva et al, 2022 ; Musa et al, 2022 ; Toga et al, 2021 )–– ( Al-qaness et al, 2020 ; Benvenuto et al, 2020 ; Ceylan, 2020 ; Chakraborty & Ghosh, 2020 ; Dobreva et al, 2022 ; Musa et al, 2022 ; Toga et al, 2021 ). Most of these works were based on publicly available data, generally reported by public health authorities in an aggregated form.…”
Section: Discussionmentioning
confidence: 99%
“…We also found that most respondents had received more than one dose, although about 1 in 10 had only received the first dose, suggesting additional outreach is needed to make sure everyone is fully vaccinated. As vaccine immunity wanes and new variants emerge, continued messaging, new vaccinations, and uptake of other non-pharmaceutical interventions to prevent transmission will be critical 48 49. Studies to understand how to improve governance to increase vaccination and to determine optimal levels of vaccination are important to inform policy 50–52.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we found that prioritizing booster vaccination for people aged 19-58 years avoided the largest infection cases and was the most cost-effective. Based on sociological surveys, 19-58 years old people were found that they have more unprotected close contact and are at greater risk of COVID-19 infection compared to those aged 0-18 and 58+ years due to work etc., [12] and the booster vaccination provides additional protection compared to one-dose vaccination. Thus, our conclusion is justified.…”
Section: Main Findingsmentioning
confidence: 99%